Cognitive Metaphors of the Mind in "The Canterbury Tales" - Wawrzyniak, Agnieszka (Research in Language, 2014)
The paper presents an analysis of a number of cognitive metaphors pertaining to the concept of mind (e.g. sanity and insanity), heart, and fire. The study has been based on the text of Canterbury Tales by Geoffrey Chaucer. The paper contains a short theoretical introduction and a discussion of different linguistic and psychological approaches to issues related to figurative and literal, conventional language use. The analytical part focuses on the detailed contextual study of the cognitive metaphorical concepts. It is argued that many apparently similar concepts can evoke semantically conflicting metaphors, while concepts that appear to be mutually exclusive can sometimes evoke common associations and thereby similar metaphors.